#nofilter: Online Personas and The Negative Impacts of Social Media on Young Adults’ Self-esteem - Jessica Godwin (Institute of Research and Community Outreach - Petra Christian University, 2019)
My novel #nofilter follows Mia, a photo model who is pretty famous on the social media platform Instagram, as she meets Kyle, her online boyfriend for the first time. In an effort to earn other people’s acceptance, Mia has been building a perfect online persona. However, after meeting Kyle, it is revealed that she is not who she portrays herself to be. As my work revolves on how social media affects someone’s self-esteem, hopefully it can help the readers learn to love themselves and do not depend their self-esteem on others. Specifically, I focus on how Mia maintains an idealized online persona in order to cope with her low self-esteem and earn other people’s acceptance, how the contrast between Mia’s online and real life personas causes her relationship with Kyle to crumble, and how Mia learns to love herself by accepting her weaknesses and acknowledging her positive qualities. For that reason, I use Contingencies of Self-esteem theory by Jennifer Crocker and Connie T. Wole, the Social Comparison theory, and the Presentation of Self in Everyday Life by Erving Goffman. Set in the early years after college, I use New Adult genre and the sub-genre Contemporary Romance to explore Kyle and Mia’s romantic relationship. Keywords: Social media, Instagram, self-esteem, online persona, New Adult, Contemporary Romance